2023
DOI: 10.1159/000533191
|View full text |Cite
|
Sign up to set email alerts
|

Management of Status Epilepticus by Different Pediatric Departments: Neurology, Intensive Care, and Emergency Medicine

Özge Dedeoglu,
Halise Akça,
Serhat Emeksiz
et al.

Abstract: <b><i>Introduction:</i></b> The aim of this study was to explore the differences in status epilepticus (SE) management among pediatric neurology, emergency medicine, and intensive care specialists in Turkey. <b><i>Methods:</i></b> A 22-item questionnaire regarding first-, second-, and third-line management strategies of SE including demographic characteristics and common etiologies according to the specialty of participants was mailed to 370 specialists working i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Until recently phenytoin was commonly used second-line ASM. 3 , 5 , 13 , 14 However, two recent large randomized controlled trials (RCTs) compared the efficacy of levetiracetam and phenytoin as second-line ASM in PSE and noted that levetiracetam is equally effective and safe second-line ASM. 7 , 8 However, due to safety profile and comparative ease of administration, it was suggested that levetiracetam could be an appropriate alternative to phenytoin as second-line ASM in PSE.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Until recently phenytoin was commonly used second-line ASM. 3 , 5 , 13 , 14 However, two recent large randomized controlled trials (RCTs) compared the efficacy of levetiracetam and phenytoin as second-line ASM in PSE and noted that levetiracetam is equally effective and safe second-line ASM. 7 , 8 However, due to safety profile and comparative ease of administration, it was suggested that levetiracetam could be an appropriate alternative to phenytoin as second-line ASM in PSE.…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of SRSE, about half of intensive care specialists and neurologists preferred to use immunomodulation and 60% neurologists preferred ketogenic diet. 14 Another survey from Argentina (252 participants; 77% pediatricians and 16% intensive care specialists) demonstrated that most participants preferred midazolam infusion as third-line ASM (63%) and only 17% preferred thiopentone infusions. 13 The preference in use of midazolam infusion as third-line ASM in literature as well as in the index eSurvey is possibly due to lack of evidence for this stage of treatment, easily availability, and better adverse effect profile.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations